Pengaruh Komisaris Independen, Leverage, Ukuran Perusahaan Terhadap Audit Report Lag - F Sinta Kumala Dewi; Angelina PutriAnggraeni; Imelda Sinaga; Maria Maranatha Gultom (Universitas Teknologi Surabaya, 2026)
The timeliness of audited financial statement publication is an important indicator in assessing the quality of corporate financial reporting. Delays in the issuance of audit reports, known as audit report lag, can reduce the relevance of financial information for stakeholders. This study aims to analyze the effect of independent commissioners, leverage, and firm size on audit report lag in insurance sector companies listed on the Indonesia Stock Exchange during the 2020–2023 period. This research uses a quantitative approach with secondary data obtained from annual financial reports published on the Indonesia Stock Exchange. The data analysis technique used is multiple linear regression analysis preceded by classical assumption tests. The results indicate that leverage has a significant effect on audit report lag, while independent commissioners and firm size do not have a significant effect on audit report lag. Simultaneously, these variables influence audit report lag. This study is expected to contribute to the development of research related to factors affecting the timeliness of audit report completion.